Pengaruh Metode Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Fase E AKL SMK Negeri 1 Painan - Desi Ilona; Reni Respita; Rasyid Akmal (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to determine the difference in student learning outcomes using the Problem Based Learning (PBL) method and the conventional method in Phase E at SMK Negeri 1 Painan. By comparing these two methods, this research is expected to provide insight into the effectiveness of PBL in improving student learning outcomes. This study is a quasi-experimental research with a Nonequivalent Control Group Design. The population consists of two classes of Phase E AKL students at SMK Negeri 1 Painan in the 2025 academic year: AKL1 as the control class and AKL2 as the experimental class. Sampling was done by total sampling, and the research instrument was a learning outcomes test. The analysis showed that students taught with PBL experienced significant improvement in accounting learning outcomes. Data from both classes were normally distributed and homogeneous, so the hypothesis test used was the T-test. Based on data processed using SPSS 16.0, the significance value (Sig. 2-tailed) was 0.011, less than the 5% significance level (0.05), and the t-value (2.683) was greater than the t-table value (2.024). Therefore, the null hypothesis was rejected, concluding a significant difference in accounting learning outcomes between the PBL and conventional methods in Phase E AKL at SMK Negeri 1 Painan.